IL-1β Induced Cytokine Expression by Spinal Astrocytes Can Play a Role in the Maintenance of Chronic Inflammatory Pain - Gajtkó, Andrea; Bakk, Erzsébet; Hegedűs, Krisztina; Ducza, László; Holló, Krisztina (Frontiers in Physiology, 2020)
It is now widely accepted that the glial cells of the central nervous system (CNS) are key players in many processes, especially when they are activated via neuron-glia or glia-glia interactions. In turn, many of the glia-derived pro-inflammatory cytokines contribute to central sensitization during inflammation or nerve injury-evoked pathological pain conditions. The prototype of pro-inflammatory cytokines is interleukin-1beta (IL-1β) which has widespread functions in inflammatory processes and capable to induce the secretion of further inflammatory mediators. In this study our aim was to examine the effect of IL-1β on spinal astrocytes and identify those cytokines which are secreted upon IL-1β stimulation and may have a role in the maintenance of inflammatory pain. In the initial experiments we measured the IL-1β concentration in the spinal cord of C57BL/6 mice during the course of complete Freund adjuvant (CFA)-induced inflammatory pain and observed a peak of IL-1β level at the time of highest mechanical sensitivity. In order to further study astrocytic activation, primary astrocyte cultures from spinal cords of C57BL/6 wild type and IL-1R1 deficient mice were exposed to IL-1β in concentrations corresponding to the spinal levels in the CFA-induced pain model. By using cytokine array method we observed significant increase in the expressional level of three pro-inflammatory cytokines: interleukin-6 (IL-6), granulocyte-macrophage colony stimulating factor (GM-CSF) and chemokine (C-C motif) ligand 5 (CCL5 or RANTES). The overexpression of the selected cytokines was also detected in the dorsal spinal cord during the course of CFA-evoked inflammatory pain. By inhibiting the NF-kB pathway we could block the IL-1β-induced over-production of the three cytokines in the spinal astrocytes. Our data complements the picture of the IL-1β-triggered cytokine release of spinal astrocytes during inflammatory pain. The secretion of these mediators may lead to the enhanced activity of the local cells (neurons and glia as well) and can lead to the prolonged activation of the spinal nociceptive circuits. All three of the selected cytokines and the NF-kB pathway can be possible targets for future studies to clarify the mechanism of the intercellular communication in the spinal dorsal horn during chronic pain conditions.